2015
DOI: 10.1007/s10681-015-1525-x
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping and candidate gene analysis of a novel PANICLE AND SPIKELET DEGENERATION gene in rice

Abstract: To better understand the molecular mechanisms that regulate inflorescence and flower architecture, we characterized the rice panicle and spikelet degeneration (psd) mutant, which exhibited small panicles with a reduced number of primary and secondary branches. The psd mutant had few spikelets per panicle, and they were deformed and could not form seeds. The psd mutant had a unique panicle organization phenotype that was not present in other aberrant panicle organization mutants. Genetic analysis revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Beside Arabidopsis thaliana , the physiological functions of FRS family members have not been investigated in other higher plant groups. However, recent studies have suggested that putative FRS members are the candidate genes for Panicle and Spikelet Degeneration ( PSD ) gene in rice ( Zhang et al, 2015 ), and a photoperiod-dependent flowering time regulator in wheat ( Kiseleva et al, 2017 ). In addition, genomic sequencing and population genomic analysis of silver birch ( Betula pendula ) also demonstrated that a putative FRS10 member might be the candidate gene correlated with the adaptation to environment ( Salojarvi et al, 2017 ).…”
Section: Physiological Functions Of Frs-frf Family Proteinsmentioning
confidence: 99%
“…Beside Arabidopsis thaliana , the physiological functions of FRS family members have not been investigated in other higher plant groups. However, recent studies have suggested that putative FRS members are the candidate genes for Panicle and Spikelet Degeneration ( PSD ) gene in rice ( Zhang et al, 2015 ), and a photoperiod-dependent flowering time regulator in wheat ( Kiseleva et al, 2017 ). In addition, genomic sequencing and population genomic analysis of silver birch ( Betula pendula ) also demonstrated that a putative FRS10 member might be the candidate gene correlated with the adaptation to environment ( Salojarvi et al, 2017 ).…”
Section: Physiological Functions Of Frs-frf Family Proteinsmentioning
confidence: 99%
“…Tetra-primer ARMS PCR is rapid, simple, and economical. According to the SNP site, the tetra-primer ARMS PCR technique has been used to identify various germplasm genotypes in rice, wheat, capsicum, and other crops [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on Arabidopsis FHY3 and FAR1 has clarified the vital roles of FRSs in plant growth and development [54]. There are ongoing studies on the FRSs in several species, such as rice, wheat, tomato, cotton, tea, eucalyptus, silver birch (Betula pendula) and Tibetan Prunus [30][31][32]53,55,[57][58][59]. In the present study, we identified StFRS family members in potato for the first time, identified the biological pathways in which they might participate, and focused on their roles in the abiotic stress response.…”
Section: Discussionmentioning
confidence: 99%